2019
DOI: 10.7567/1347-4065/ab516e
|View full text |Cite
|
Sign up to set email alerts
|

SOI wafer fabricated with extremely thick deposited BOX layer using a surface activated bonding technique at room temperature

Abstract: The fabrication cost of bonded silicon on insulator (SOI) wafers for customized power devices is high owing to the high temperature required and the very long fabrication process involving both thermal oxidation and bonding. In addition, SOI wafers are contaminated with metallic impurities during the formation of the buried oxide (BOX) layer and the bonding of a silicon layer on the BOX layer. Therefore, we propose an alternative SOI wafer fabrication method combining BOX layer deposition and surface activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…44) In addition, according to previous studies, SAB can fix not only crystalline materials but also noncrystalline materials. 21,31,45) Our results are thus reasonable. 24,29,30) Therefore, we concluded that a silicon wafer (layer) could be fixed to a SiC layer with a capping SiN layer of a base wafer without voids or punch-out dislocations larger than 1 nm by depositing the amorphous adhesive layer containing silicon before bonding.…”
Section: Evaluation and Observation Of Voids Formed Whensupporting
confidence: 80%
See 1 more Smart Citation
“…44) In addition, according to previous studies, SAB can fix not only crystalline materials but also noncrystalline materials. 21,31,45) Our results are thus reasonable. 24,29,30) Therefore, we concluded that a silicon wafer (layer) could be fixed to a SiC layer with a capping SiN layer of a base wafer without voids or punch-out dislocations larger than 1 nm by depositing the amorphous adhesive layer containing silicon before bonding.…”
Section: Evaluation and Observation Of Voids Formed Whensupporting
confidence: 80%
“…A reference sample was fabricated by the PE-CVD of SiO 2 as the insulator layer at 500 °C and fixed by SAB at room temperature. 31)…”
Section: Sample Preparationmentioning
confidence: 99%
“…We firstly studied the SOI wafer with the BOX layer formed by CVD at 500 °C, in order that this layer was dense. 37) This wafer had good characteristics that were a bonding interface and a breakdown electrical field. However, because a CVD process is normally at below 400 °C, the CVD device used at 500 °C has special specs and must be made to order.…”
Section: Introductionmentioning
confidence: 99%